Determination in the Anatolian Hieroglyphic Script: The Late 10th and Early 9th Centuries BC - Payne, Annick (Altorientalische Forschungen, 2018)
The Anatolian Hieroglyphic script is a mixed writing system which contains both phonetic and semantographic signs. The latter may be used in the function of logogram and/or determinative. The study of hieroglyphic signs used as determinatives contributes to our understanding of the writing system, its structures and development over time, as well as categories of mental organization. This article forms the second part of a diachronic study of the determinative system, and addresses the period from the late 10 th to early 9 th century BC.